Astro‐logics with microRNAs. (3rd March 2015) - Eitan, Chen; Hornstein, Eran
<x xml:space="preserve">Abstract</x> Astrocytes are a subtype of glial cells in the central nervous system that are critical for normal brain activity. In this issue of The EMBO Journal, Shenoy et al provide evidence for the involvement of miRNAs in the molecular mechanism underlying the in vitro differentiation of astrocytes from glial progenitor cells. Let‐7 and miR‐125 jointly silence multiple mRNA targets that would have potentially disrupted differentiation if expressed, and function in concert with JAK‐STAT signaling to promote astrocyte differentiation.